Effect of bilateral salpingectomy with hysterectomy on ovarian reserve - Singh, Shakun; Bhavana, Rudavath; Chaudhary, Rachna; Dhama, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Aim of the study was to evaluate the effect of salpingectomy with hysterectomy on ovarian reserve. Methods: This prospective case control study was done in the department of obstetrics and gynaecology from June 2020 to May 2021 on patients who underwent hysterectomy with or without salpingectomy were included in the study. Patients then divided into two groups of 30 in each group. In group A hysterectomy without salpingectomy were included. In group-B patients who underwent hysterectomy with salpingectomy were included, and then both groups were followed through Si-anti-Mullerian hormone (AMH), luteinizing hormone (LH), follicle stimulating hormone (FSH) and ovarian volume. Results: Baseline AMH levels were 1.20 ng/mL for group-A, 1.29 ng/mL for group-B with no statistical significance. It was seen that AMH levels for across the group but of no statistical significance at any given follow up-line point. Baseline LH levels were 7.22 IU/L and 7.27 IU/L for group-A and group-B patients respectively with no statistical significance. The average LH levels seen to increase in the follow up period in both groups, but it was of no statistic significant at any given follow up time point. Baseline FSH levels were 7.58 IU/L and 6.84IU/L for group A and group-B respectively with no statistical significance. The average FSH levels were seen to increase is the follow up period in both groups. Conclusions: The hysterectomy coupled with bilateral salpingectomy (BS) had minimal or no statistically significant impact on the ovarian reserve. Depends on patients’ profile and states of fallopian tube we should take decision of salpingectomy during surgery.